If it's not what You are looking for type in the equation solver your own equation and let us solve it.
*x2-3=12
We move all terms to the left:
*x2-3-(12)=0
We add all the numbers together, and all the variables
x^2-15=0
a = 1; b = 0; c = -15;
Δ = b2-4ac
Δ = 02-4·1·(-15)
Δ = 60
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{60}=\sqrt{4*15}=\sqrt{4}*\sqrt{15}=2\sqrt{15}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{15}}{2*1}=\frac{0-2\sqrt{15}}{2} =-\frac{2\sqrt{15}}{2} =-\sqrt{15} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{15}}{2*1}=\frac{0+2\sqrt{15}}{2} =\frac{2\sqrt{15}}{2} =\sqrt{15} $
| x/3-1/4=4/3 | | 8(x+3)+4(x+3)=7x-7 | | 38.47+.50x=x | | 6y+9=2y-1 | | 6-12x=102 | | -12a+a=-11a-3 | | 15x-10=-9x=2 | | 0.25(x+40)-0.07(x-60)=12.4 | | 2/5x+(x+1)/x=2 | | 10+3z=-10–2z–5z | | 0=-3x+5 | | -4c-11=4c+22 | | 9x-7=-3(2x-1) | | 8x2−48=0 | | 5y+14=26 | | 5u+15=95 | | 8d+3=-1+4d | | 2(5x+2)+3=-43 | | (2w-3/5)-(4-w/2)+1=w+1/3 | | x/12-4=3/4 | | -5(p+3/5)=- | | -4y-2=-3y | | 2/5×15=3/5x-6 | | y/12+3=-10 | | -4y–2=-3y | | x/2-1/5=1/2 | | -7w+8=w | | 2(z-8)+3z=4 | | x-1/3=17/12 | | 8+4v=3v | | 5(y-8)+3y=40 | | -10+u=10-4u |